2019
DOI: 10.6028/jres.124.015
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Computed Tomography Instrument Performance Evaluation, Part II: Sensitivity to Rotation Stage Errors

Abstract: The development of standards for evaluating the performance of X-ray computed tomography (XCT) instruments is ongoing within the American Society of Mechanical Engineers (ASME) and the International Organization for Standardization (ISO) working committees. A key challenge in developing documentary standards is to identify test procedures that are sensitive to known error sources. In Part I of this work, we described the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Processing each individual simulated dataset is an unreasonably inefficient approach, both in terms of the requirements for data storage and data processing. Muralikrishnan et al [73,74] presented a computationally efficient single point ray tracing method that can be used to determine the contribution of geometrical instrument errors to errors in the x-ray CT measurement of point-to-point distance measurements for simple geometrical features, e.g. spheres.…”
Section: Componentmentioning
confidence: 99%
“…Processing each individual simulated dataset is an unreasonably inefficient approach, both in terms of the requirements for data storage and data processing. Muralikrishnan et al [73,74] presented a computationally efficient single point ray tracing method that can be used to determine the contribution of geometrical instrument errors to errors in the x-ray CT measurement of point-to-point distance measurements for simple geometrical features, e.g. spheres.…”
Section: Componentmentioning
confidence: 99%
“…We calculated the outer ring radius R of the reference object and the radius r of the individual spheres in that object and determined the center locations of each of the 125 spheres. We then used the single-point ray tracing method (described in [1][2]) to determine the sphere centers of the reconstructed object in the presence of the detector X location error of 0.1 mm. We calculated sphere center-to-center distance errors for all pairs of spheres and the form error for each of the 125 spheres.…”
Section: Simulation Proceduresmentioning
confidence: 99%
“…In two prior National Institute of Standards and Technology (NIST) Journal of Research publications (Parts I and II [1,2]), we focused on one error source, geometry errors in conebeam XCT systems, and its effect on dimensional measurements. Geometry errors include errors associated with the position and pose of the detector, position of the rotation stage, and error motions of the rotation stage (such as axial, radial, wobble, and scale (angular indexing) errors).…”
Section: Introductionmentioning
confidence: 99%
“…We then utilized this technique to describe the effect of detector geometry errors on the sphere center-to-center distance error and sphere form error. In Part II of this series [ 16 ], we focused on the effect of rotation stage errors on the sphere center-to-center distance error and sphere form error, again using SPRT. Those studies identified the placement of spheres in the measurement volume so that each of the error sources could be captured most effectively, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we identified the need to extend the studies in Parts I and II to cover the working range of an XCT system with a movable detector so that we may provide more specific guidance to documentary standards committees developing these documents and to users of such systems that want to establish whether their instrument meets the manufacturer’s specifications. In this Part III, we extend the work done in the first two parts [ 15 16 ] by repeating the SPRT simulations for several combinations of d and D . We discussed some early results in Ref.…”
Section: Introductionmentioning
confidence: 99%